Extra-cerebral recombination activity of Emx1-Cre and nestin-Cre in the kidney - Wang, Min; Liu, Xiaojuan; Fang, Yin; Li, Qintong (Frontiers in Cell and Developmental Biology, 2024)
Individuals with neurodevelopmental disorders (NDDs) are frequently diagnosed with comorbidities in other organs, indicating that NDD risk genes may have extra-cerebral functions.The engineered mouse models are pivotal in understanding the functions of candidate NDD genes.Here, we report that Emx1-Cre and nestin-Cre mouse strains, the popular tools to study brain development, also exhibit recombination activity in the kidney. We find that both Emx1-Cre and nestin-Cre can drive recombination in epithelial cells lining proximal and distal convoluted tubules of the nephron. Additionally, nestin-Cre drives recombination in the glomerulus of the nephron. Furthermore, we use Emx1-Cre and nestin-Cre to knock out Larp7, a gene linked to a human NDD called Alazami syndrome. We find that Larp7 knockout using nestin-Cre, but not Emx1-Cre, results in elevated blood urea nitrogen. This result suggests a compromised kidney function, reminiscent of recently revealed renal anomalies in Alazami syndrome patients. Many genes have been knocked out using Emx1-Cre and nestin-Cre to study their roles during embryonic neurogenesis. It will be of great interest to reinvestigate whether the renal development and function is affected in these existing mouse models.